PEMANFAATAN FENOMENA ALAM GUNUNG GALUNGGUNG SEBAGAI SUMBER BELAJAR UNTUK MENGEMBANGKAN DAYA ANALISIS MAHASISWA GEOGRAFI: PEMANFAATAN FENOMENA ALAM GUNUNG GALUNGGUNG SEBAGAI SUMBER BELAJAR UNTUK MENGEMBANGKAN DAYA ANALISIS MAHASISWA GEOGRAFI - Erwin Hilman Hakim (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2017)
Natural phenomena Mountain Galunggung learning resources in understanding the symptoms of volcanism, these phenomena can be used as a source of learning geography student to improve the analysis of their environment. Geography is a natural laboratory and a lot of geography materials that can not be understood simply by studying a concept in the literature book is done in space by verbalistis. This research was conducted at the Department of Geography Students of the Faculty of Education Siliwangi University. This study population Geography students the semester II of classes using model experiments with field studies and grade control using model lecture. Quantitative data analysis techniques using statistical methods, there are two statistical techniques used, namely descriptive statistics for the description of research data and statistical techniques t-test. There is a significant difference to the results of the test and development of power analysis geography student this is evidenced by the results of tests experimental minimum 13, maximum numbers 23, the range of values 10, a mean of 18.15, median 18.00. The test results control class minimum 10, maximum 20, the range of values 10, mean 15.39, median 15.00. Power analysis geography student experiment class has a depth analysis of the phenomena that is the result of data processing that students can open up and develop the power of analysis, the material is easy to understand, the students more active and interactive, while for the control class learning process is less effective without a concrete example to be analytical.